Sistem Informasi Geografis Pemetaan Tempat Ibadah Pada Pulau Bali Berbasis Mobile - Rifky Lana Rahardian; I Gusti Ngurah Dwiky Widiastra; I Made Kresna Negara (Politeknik Negeri Cilacap, 2020)
In making a vacation trip, sometimes tourists will visit a place that is a tourist spot, but it does not rule out the tourists will look for a place of worship to carry out their worship activities or just to visit. The place of worship is one of the locations that are often sought by local and foreign tourists when they are on vacation. A place of worship is a place devoted to praying and offering prayers to God Almighty. The importance of this research is because tourists sometimes find it difficult to find the right place of worship and find information in it, a common difficulty encountered by tourists is the lack of information provided in the place of worship. Purpose Geographical information system mapping places of worship on Bali-based mobile is a mapping application of places of worship where users can find out the location of places of worship that are nearby or that the user is looking for, users can also find out events in the place of worship every day so local and foreign tourists who come to visit the island of Bali is not difficult to find a place of worship to carry out their worship activities. Research conducted using the waterfall method.